Knowledge and sources of information about medicines among adolescents in Malta - Darmanin Ellul R; Cordina M; Buhagiar A; Fenech A; Mifsud J (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Objective: To investigate knowledge of medicines and sources of information about medicines among adolescents in Malta.Methods: A self-administered questionnaire was used to survey knowledge of medicines and information sources among adolescents attending secondary schools in Malta. A random stratified sample design generated a sample size of 514 students. Knowledge of medicines was investigated by questions that included topics about the efficacy of medicines, proper communication during a medical consultation, the safety of medicines, antibiotic use and pictograms. Results: The analytical sample, of which 53.8% were girls, was made up of 474 students, aged 14-16 years. The students obtained a mean score of 22.92 points (SD = 4.31) out of a maximum of 32 points for medicine knowledge. More than 30.0% of the respondents did not mark the correct answer for 40.6% of the questions that investigated knowledge of medicines. The family physician, community pharmacist and parents were the sources of information that were mostly cited. A proportion of 4.4% had obtained information from the teacher. A quarter of the respondents (24.7%) had obtained information from friends/schoolmates, young relatives or the media, generally television (17.3%). Conclusion: Although the level of knowledge about medicines among this study sample of Maltese students was good, there appeared to be particular misconceptions with regard to important aspects associated with the proper use of medicines. These findings highlight the need to educate adolescents about the proper use of medicines. The most important information providers about medicines appeared to be the physician, pharmacist and parents. It is being suggested that education campaigns should be organized in order to help parents guide adolescents on how to use medicines appropriately. In addition, adolescents would benefit if more information about the proper use of medicines would be disseminated by means of television programs and school-based health education curricula.